An Unusual Cause of Pseudomedian Nerve Palsy - Zina-Mary Manjaly; Andreas R. Luft; Hakan Sarikaya (Case Reports in Neurological Medicine)
We describe a patient who presented with an acute paresis of her distal right hand suggesting a peripheral median nerve lesion. However, on clinical examination a peripheral origin could not be verified, prompting further investigation. Diffusion-weighted magnetic resonance imaging revealed an acute ischaemic lesion in the hand knob area of the motor cortex. Isolated hand palsy in association with cerebral infarction has been reported occasionally. However, previously reported cases presented predominantly as ulnar or radial palsy. In this case report, we present a rather rare finding of an acute cerebral infarction mimicking median never palsy.